1993
DOI: 10.1093/ajcn/57.6.875
|View full text |Cite|
|
Sign up to set email alerts
|

Dietary fat and serum lipids: an evaluation of the experimental data

Abstract: Regression analysis of the combined published data on the effects of dietary fatty acids and cholesterol on serum cholesterol and lipoprotein cholesterol evaluated with groups of human subjects shows that 1) saturated fatty acids increase and are the primary determinants of serum cholesterol, 2) polyunsaturated fatty acids actively lower serum cholesterol, 3) monounsaturated fatty acids have no independent effect on serum cholesterol and, 4) dietary cholesterol increases serum cholesterol and must be considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
210
1
7

Year Published

1997
1997
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 458 publications
(235 citation statements)
references
References 86 publications
17
210
1
7
Order By: Relevance
“…The in¯uences of dietary fat on serum cholesterol have been studied extensively, and there is universal agreement that a reduction in dietary saturated fat will lower serum total and low density lipoprotein (LDL) cholesterol (Grundy & Denke, 1990;La Rosa et al, 1990;Mensink & Katan, 1992;Hegsted et al, 1993;NCEP Expert Panel, 1993;Katan et al, 1994). There is, however, no agreement as to which nutrients should replace saturated fatty acids.…”
Section: Introductionmentioning
confidence: 99%
“…The in¯uences of dietary fat on serum cholesterol have been studied extensively, and there is universal agreement that a reduction in dietary saturated fat will lower serum total and low density lipoprotein (LDL) cholesterol (Grundy & Denke, 1990;La Rosa et al, 1990;Mensink & Katan, 1992;Hegsted et al, 1993;NCEP Expert Panel, 1993;Katan et al, 1994). There is, however, no agreement as to which nutrients should replace saturated fatty acids.…”
Section: Introductionmentioning
confidence: 99%
“…By the 1960s, it was clear that several dietary components had sizable effects: higher intake of cholesterol and saturated fatty acids (SFA) raises serum cholesterol on average; calorie imbalance (on 'Western' fare) with weight gain also raises serum cholesterol; in contrast, higher intake of polyunsaturated fatty acids (PFA) and watersoluble fibre have moderate cholesterol-lowering effects, as does weight loss by obese people consuming fat-modified fare. [7][8][9][10][11] Extensive evidence demonstrating these dietary influences has been from the early 1960s on the scientific foundation for repeated recommendations by expert groups that the general population improve eating patterns to lower serum cholesterol. [12][13][14][15][16][17][18][19] More recently, data on adverse effects of dietary trans fatty acids on serum cholesterol led to expansion of recommendations to encompass avoidance of foods with these components.…”
mentioning
confidence: 99%
“…The regression equation for LDL cholesterol showed a signi®cant negative (namely, lowering) coef®cient for polyunsaturates, not for MUFA (Table 1). Hegsted et al (1993) included the whole literature, including early papers that only reported total cholesterol, with a few exceptions: formula diets or very short experimental periods. They separately analysed 50 papers reporting metabolic ward experiments and 37 ®eld study experiments, and focused on serum total cholesterol.…”
mentioning
confidence: 99%
“…A possibility mentioned in discussion by a few authors (Hegsted et al, 1993;Gardner & Kraemer, 1995) is that average samples of speci®c plant oils rich in MUFA might differ somewhat in their effect on plasma cholesterol. While investigating the possibility that palmitic acid (16:0), and hence palmolein, may be less cholesterolraising than myristic and lauric acids and oils rich in these (Hayes et al, 1991) we happened to compare in turn, in three separate sets of human experiments (21± 42 subjects per experiment) plasma total, LDL and HDL cholesterol on palmolein against three MUFA rich oils: canola, olive and high-oleic sun¯ower oils.…”
mentioning
confidence: 99%